2016
DOI: 10.1021/acs.est.5b06121
|View full text |Cite
|
Sign up to set email alerts
|

Assessing PM2.5Exposures with High Spatiotemporal Resolution across the Continental United States

Abstract: A number of models have been developed to estimate PM2.5 exposure, including satellite-based aerosol optical depth (AOD) models, land-use regression or chemical transport model simulation, all with both strengths and weaknesses. Variables like normalized difference vegetation index (NDVI), surface reflectance, absorbing aerosol index and meteoroidal fields, are also informative about PM2.5 concentrations. Our objective is to establish a hybrid model which incorporates multiple approaches and input variables to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
326
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 423 publications
(338 citation statements)
references
References 79 publications
(153 reference statements)
12
326
0
Order By: Relevance
“…The results are in line with other recent studies [52][53][54], which all indicated that land use information such as NDVI can help to predict the PM 2.5 concentration.…”
Section: Model Validationsupporting
confidence: 92%
“…The results are in line with other recent studies [52][53][54], which all indicated that land use information such as NDVI can help to predict the PM 2.5 concentration.…”
Section: Model Validationsupporting
confidence: 92%
“…A similar hybrid approach has been applied to assess human exposures to PM 2.5 mass and chemical components (Di et al 2015, Di et al 2016, Kloog et al 2014, Kloog et al 2011). This study applies a hybrid approach similar to the previous model of PM 2.5 , but incorporates additional variables due to ozone’s distinct gaseous nature and chemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Details have been published elsewhere. 12,13 Warm season is defined to be from April 1 to September 30, which is the specific time window to examine the association between ozone and mortality. Meteorological variables including air and dew point temperatures were retrieved from North American Regional Reanalysis data and estimated daily mean values were determined for each 32 km × 32 km grid in the continental US.…”
Section: Methodsmentioning
confidence: 99%